Issues of Increasing Budget Revenues in Ensuring Socio-Economic Development of Regions - Iskandarov Abdurasul Mirjalil ugli; Egamberdiyev Murodulla Farkhod ugli (Scientific Trends, 2024)
This article describes the structure of local budgets in Uzbekistan, their structure, and the practice of financing local budgets' incomes and expenses. In recent years, the movement of local budget funds has been studied on the scale of the regions, the city of Tashkent and the Republic of Karakalpakstan. it is appropriate to come out and put them into practice.
Keywords: Local budget, budget process, income, expenditure, tax, financial transfer, social payment, levy, rent payment..